2015
DOI: 10.1016/j.tube.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The antimicrobial effect of colistin methanesulfonate on Mycobacterium tuberculosis in vitro

Abstract: Please cite this article in press as: van Breda SV, et al., The antimicrobial effect of colistin methanesulfonate on Mycobacterium tuberculosis in vitro, Tuberculosis (2015), http://dx.doi.org/10.1016/j.tube.2015.05.005 SUMMARYPolymyxins have previously been described to have activity against M. tuberculosis (MTB), but further research was abandoned due to systemic toxicity concerns to achieve the required MIC. Colistin methanesulfonate (CMS), a polymyxin, is well tolerated when inhaled directly into the lungs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…We found that AS-48 is bactericidal against M. tuberculosis. Several other bacteriocins have been reported as effective against M. tuberculosis in in vitro assays (7,(21)(22)(23): colistin has a MIC of 16 g/ml (24), and nisin showed a MIC of Ͼ60 g/ml against M. tuberculosis H37Ra (7). The authors described variants of nisin with an enhanced antimicrobial activity (22) against M. tuberculosis as well as other naturally occurring bacteriocins such as lacticin 3147 (MIC 90 of 7.5 g/ml) (7).…”
Section: Discussionmentioning
confidence: 99%
“…We found that AS-48 is bactericidal against M. tuberculosis. Several other bacteriocins have been reported as effective against M. tuberculosis in in vitro assays (7,(21)(22)(23): colistin has a MIC of 16 g/ml (24), and nisin showed a MIC of Ͼ60 g/ml against M. tuberculosis H37Ra (7). The authors described variants of nisin with an enhanced antimicrobial activity (22) against M. tuberculosis as well as other naturally occurring bacteriocins such as lacticin 3147 (MIC 90 of 7.5 g/ml) (7).…”
Section: Discussionmentioning
confidence: 99%
“…One potentially novel intervention being investigated to reduce infectiousness during end-of-life care is the use of the inhaled antibiotic, dry powder colistin, commonly used for patients with cystic fibrosis. 502 …”
Section: The Lancet Respiratory Medicine Commissionmentioning
confidence: 99%
“…Little is known about the early bactericidal activity of inhalation of anti-TB drugs. The first report studying the effect of inhalation of colistin on transmission of TB, however, unfortunately not an EBA study, was presented at the Union conference in Vancouver in 2013 [117,118]. Theoretically, inhalation of a drug can produce high concentrations at the site of infection .…”
Section: Five-year Viewmentioning
confidence: 99%